Benefits of Virgin Coconut Oil in Diet to Colossoma macropomum (Cuvier, 1818) - Márcia Valéria Silva do Couto; Natalino da Costa Sousa; Higo Andrade Abe; Joel Artur Rodrigues Dias; Carlos Alberto Martins Cordeiro; Peterson Emmanuel Guimarães Paixão; Thays Brito Reis Santos; Fernanda dos Santos Cunha; Juliana Oliveira Meneses; Ricardo Marques Nogueira Filho; Carol Nunes Costa Bomfim; Cláucia Aparecida Honorato; et al. (Aquaculture Nutrition)
This study investigated the effects of different dietary levels of virgin coconut oil on growth, body composition, bacterial resistance, and hematology parameters in tambaqui (Colossoma macropomum). Six isolipidic (12% crude lipid) and isonitrogenous (33% CP) diets were formulated adding virgin coconut oil (0%, 25%, 50%, 75%, and 100%) as lipid source, replacing the soybean oil. A positive control diet also prepared containing 15% lauric acid (main fatty acid in virgin coconut oil). Triplicate groups of 20 fish were fed twice daily throughout 90 days. Monthly, we evaluated the tambaqui growth performance, weight and biomass gain, specific growth ratio, apparent feeding conversion, relative condition factor, fish weight uniformity, and final survival. At end of experiment, the fish were subjected to bacterial challenge and blood analysis (glucose, lactate, plasmatic protein, and red cell blood). Fish fed 0%, 100% of VCO and lauric acid presented lower growth than fish fed 50% of virgin coconut oil (VCO) which presents the highest biomass (929.8±80.6a) and weight gain (15.4±4.3a) (p<0.05). Furthermore, the fish fed 50% and 75% VCO had an increase on body protein (50 and 58%, respectively) without increase body fat content. The values of triglycerides and cholesterol decreased (242.4±39.1c and 181.5±14.6bc) in fish fed 50% VCO and lauric acid, respectively. After bacterial challenge, a hemolytic anemia occurred in fish submitted to diets containing 100% of soybean oil and 100% of VCO, causing 41.67% and 100% of mortality, respectively. However, fish fed with 25 and 50% of VCO not presented any clinical signs of disease or mortality. In conclusion, dietary inclusion of 50% virgin coconut in substitution to soybean oil as a lipid source in diets for C. macropomum is recommended to improve the growth performance, body protein, and resistance against pathogenic bacteria Aeromonas hydrophila.